The first record of dermochelyid turtles in the Eocene of Tierra del Fuego: New insights on the evolution of the Weddellian faunas - Bona, Paula; Sterli, Juliana; de la Fuente, Marcelo Saul; Olivero, Eduardo Bernardo; Fernández, Marta Susana; Reguero, Marcelo Alfredo
The Antarctic Paleogene marine fossil record has been the key to reconstructing the evolution of the Weddellian Sea andfinal dismemberment of Southern Gondwana. In this context, Eocene marine vertebrates from Seymour (Marambio) Island haveprovided valuable information. We present the first Eocene record of marine reptiles from the southern Atlantic Coast of SouthAmerica. This corresponds to several postcranial turtle remains represented by a proximal end of the right humerus, three caudal andone thoracic vertebrae, a fragment of the left pubis, and ten ossicles of the dorsal carapace, coming from the Leticia Formation(late-mid Eocene) at Cabo Tiburones, Tierra del Fuego, Argentina. These materials show several features such as the size and generalmorphology of the humerus and vertebrae, and the presence of relatively small, irregular, smooth, and unkeeled ossicles, which allowus to assign them to Dermochelyidae indet. Dermochelyids are a cosmopolitan group of cryptodiran turtles, registered from the lateCretaceous up to the recent, with some physiological-biological peculiarities (e.g., endothermy and an exclusive jellyfish-based diet)and characterized by the presence of an osseous carapace formed by ossicles. The new finding from the Leticia Formation is anaddition to the scarce and extremely fragmentary record of Eocene dermochelyids from the southern seas like those from the LaMeseta and Submeseta formations (Antarctica) and the Waihao and Burnside formations (New Zealand). This new information allowsus to discuss the presence of these turtles in such high latitudes in the past and its implication in the evolution of the Weddellian fauna. Fil: Bona, Paula. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Sterli, Juliana. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Museo Paleontológico Egidio Feruglio; Argentina Fil: de la Fuente, ...